Evaluation and Modeling of Green Energy Consumption in North Sumatra, Indonesia - Napitupulu, Janter; Suwarno, Suwarno; Cahyadi, Catra Indra; Sukarwoto, Sukarwoto (International Journal of Energy Economics and Policy, 2024)
This paper discusses the level of green energy consumption in North Sumatra from 2020 to 2022 using the entropy method, the breakpoint method, and the integrated method. These three methods are applied to determine the feasibility of using new renewable energy. The three methods will be compared to each other to determine accuracy and options for analyzing models in the future. The level of green energy users from 2020 to 2022 generally shows a relatively stable and sustainable upward trend. During the 3 years there were fluctuations caused by the large growth rate of total energy consumption in North Sumatra, which increased by 6.35% from the previous year, and the level of urban green energy consumption grew steadily, which provided a more stable increase in user levels green energy with a sharp increase in the previous year. However, there are significant gaps in green energy consumption levels between cities. The contribution of this research is to select a model that will be applied in North Sumatra and provide input for policymakers regarding future energy and can have a positive impact on technological innovation, industry, and financial support in particular.